Crisis Integration with Acceptance and Commitment Therapy Theory and Practice. - Carlsson, Katrina (American Psychiatric Association Publishing, 2023)
"Deftly combining crisis science, evolutionary psychology, neuroscience, and behavioral psychology, Crisis Integration With Acceptance and Commitment Therapy: Theory and Practice provides mental health clinicians with an easy to learn, simple to remember, and immediately actionable approach to helping patients deal with crises and evolve through them. This volume examines findings from the scientific study of crisis, offering readers a translational and functional definition of crisis and tying the acceptance and commitment therapy (ACT) model to the literature. Engaging clinical dialogues, grounded in real-world practice, demonstrate the three core processes of ACT at work in clinical practice: 1 Mindfulness and its effectiveness in both acute and chronic crises; 2 Self-compassion and how kindness to oneself during intense torment can be crucial to acceptance; and 3 Engagement with life and the importance of controlling one's own behavior amid crisis-provoking events. Although crises come in a great variety of forms, this illuminating guide posits that the core processes underpinning the generation and maintenance of a crisis response are basically the same and introduces a model that transforms moments of crisis into opportunities for learning and growth for both patients and clinicians"--